Micro‐Nano Motors with Taxis Behavior: Principles, Designs, and Biomedical Applications - Gao, Chao; Feng, Ye; Wilson, Daniela A.; Tu, Yingfeng; Peng, Fei (Small (Weinheim an der Bergstrasse, Germany), 2022)
As a novel mobile nanodevice, micro‐nano motors (MNMs) can convert the energy of the surrounding environment into mechanical motion. With this unique ability, they promise revolutionary potential in bio‐applications including precise drug delivery, bio‐sensing, and noninvasive surgery. Yet for practically reaching the target and fulfilling these tasks in dynamically changing bio‐environment, environment adaptivity beyond propulsion is important yet challenging. MNMs with taxis behavior/autonomous target‐seeking ability offer a desirable solution. These motors can adaptively move to the target location and complete the task. Thanks to the persistent efforts of researchers, tactic MNMs have shown automatic navigation to target under various energy fields, not only in static environments, but also in shear rheological conditions that simulate blood flow. Therefore, tactic motors with self‐targeting capability lay a concrete foundation for targeted drug delivery, cell transplantation, and thrombus ablation. This review systematically presents the moving principle, design, and biological applications of tactic MNMs under different energy fields. Through in‐depth analysis of state‐of‐art progress, the obstacles of the field and possible solutions are discussed. With the continuous innovation and breakthroughs of multi‐disciplinary researchers, MNMs with taxis behavior are expected to provide a revolutionary solution for cancer and other major diseases in the biomedical field. Here, an overview of recent state‐of‐art advances in micro/nanomotors is presented with tactic behavior under different energy fields. The motion principles, designs, and potential biomedical applications are presented and discussed. In addition, this review discusses in detail the taxis behavior of motors in dynamic and 3D fluid environment. Biomedical applications ranging from drug delivery, cell manipulation, and biosensing are summarized.